Surfing for social integration : mental health and well-being promotion through surf therapy among institutionalized young people - Matos, MG (2020)
Copyright: © 2017 Margarida Gaspar de Matos, et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.